2013
DOI: 10.18632/oncotarget.1148
|View full text |Cite
|
Sign up to set email alerts
|

Neratinib overcomes trastuzumab resistance in HER2 amplified breast cancer

Abstract: Trastuzumab has been shown to improve the survival outcomes of HER2 positive breast cancer patients. However, a significant proportion of HER2-positive patients are either inherently resistant or develop resistance to trastuzumab. We assessed the effects of neratinib, an irreversible panHER inhibitor, in a panel of 36 breast cancer cell lines. We further assessed its effects with or without trastuzumab in several sensitive and resistant breast cancer cells as well as a BT474 xenograft model. We confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 55 publications
(60 reference statements)
6
112
0
Order By: Relevance
“…The small tyrosine kinase inhibitor neratinib circumvents all of these problems, as supported by preclinical data in breast cancer. Data showed that treatment with neratinib had the potential to overcome resistance to trastuzumab in breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…The small tyrosine kinase inhibitor neratinib circumvents all of these problems, as supported by preclinical data in breast cancer. Data showed that treatment with neratinib had the potential to overcome resistance to trastuzumab in breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…It potently inhibits 395 HER2 and EGFR kinase activity, MAPK and AKT phos-396 phorylation, and enhances p27 induction in vitro, and 397 inhibits the growth of HER2-positive tumours in vivo [89]. 398 Unlike trastuzumab, it decreases phosphorylation of EGFR, 399 HER2, HER4 and ERK, and the addition of neratinib to 400 trastuzumab overcomes trastuzumab resistance in vitro 401 [90]. The combination of neratinib and vinorelbine has 402 shown significant antitumour effects with no synergistric 403 toxicity [91].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Neratinib significantly inhibited EGFR/HER2 kinase after binding to the ATP pocket and blocking downstream signaling pathways (59) and showed anti-cancer bioactivities in HER2-overexpression cell lines and in patients with or without prior trastuzumab treatment (66-68). Neratinib inhibited proliferation and promoted G1-S phase arrest by regulating HER2 and its downstream signaling pathways, specifically through downregulation of pEGFR, pHER2, pAKT, pMEK and pRb levels and cyclin D1 (CCND1) expression and increase of p27 levels in a HER2-dependent manner (69). Some studies also discovered that neratinib improved trastuzumab resistance and restored sensitivity to trastuzumab in HER2 + BC (69,70).…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 99%
“…Neratinib inhibited proliferation and promoted G1-S phase arrest by regulating HER2 and its downstream signaling pathways, specifically through downregulation of pEGFR, pHER2, pAKT, pMEK and pRb levels and cyclin D1 (CCND1) expression and increase of p27 levels in a HER2-dependent manner (69). Some studies also discovered that neratinib improved trastuzumab resistance and restored sensitivity to trastuzumab in HER2 + BC (69,70). Many clinical trials investigated the functions of neratinib in treating HER2…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 99%